Genetic analysis of Caenorhabditis elegans Haspin-like genes shows that hasp-1 plays multiple roles in the germline - Jommel Macaraeg; Isaac Reinhard; Matthew Ward; Danielle Carmeci; Madison Stanaway; Amy Moore; Ethan Hagmann; Katherine Brown; David J. Wynne (Biology Open, 2022)
Haspin is a histone kinase that promotes error-free chromosome segregation by recruiting the chromosomal passenger complex (CPC) to mitotic and meiotic chromosomes. Haspin remains less well studied than other M-phase kinases, and the models explaining Haspin function have been developed primarily in mitotic cells. Here, we generate strains containing new conditional or nonsense mutations in the Caenorhabditis elegans Haspin homologs hasp-1 and hasp-2 and characterize their phenotypes. We show that hasp-1 is responsible for all predicted functions of Haspin and that loss of function of hasp-1 using classical and conditional alleles produces defects in germline stem cell proliferation and spermatogenesis, and confirms its role in oocyte meiosis. Genetic analysis suggests that hasp-1 acts downstream of the Polo-like kinase plk-2 and shows synthetic interactions between hasp-1 and two genes expected to promote recruitment of the CPC by a parallel pathway that depends on the kinase Bub1. This work adds to the growing understanding of Haspin function by characterizing a variety of roles in an intact animal.